Lithium ion storage battery with high mechanical reliability
By using a combination of swelling tape and soft connecting rows on the lithium-ion battery, an elastic buffer zone and a high yield strength conduction structure is formed, which solves the mechanical damage and safety problems of lithium-ion battery in a large-scale mechanical environment, achieving high Mechanical reliability and lightweight design.
Patent Information
- Application Number
- CN202411430467.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-07
AI Technical Summary
Lithium-ion batteries are prone to mechanical damage, power outage, voltage sudden changes, performance attenuation and safety failure in large-scale mechanical environments, and the existing shock absorption design increases the weight of the battery pack, affecting energy density and performance.
采用溶胀胶带和软连接排的组合设计,溶胀胶带沿电芯外侧隔膜边缘粘贴形成弹性缓冲区,吸收电解质有机溶剂膨胀,并通过软连接排传导电流,弯折和压缩使电芯入壳装配,形成高力学可靠性结构。
It effectively reduces the mechanical magnitude, improves the radial and axial mechanical reliability of the battery cell in a large-scale mechanical environment, ensures the high performance and safety of the battery, and avoids the problem of weight increase.
Smart Images

Figure CN119275328A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium ion batteries, in particular to a lithium ion storage battery with high mechanical reliability. Background Art
[0002] With the diversification of lithium-ion battery application scenarios, batteries may face extremely harsh environmental conditions. Among them, the challenge of large-scale mechanical conditions is particularly significant in various fields of application. Lithium-ion batteries need to maintain their normal operation while coping with large-scale mechanical conditions. In a large-scale mechanical environment, the battery may suffer mechanical damage due to a decrease in the strength of the outer shell structure; the battery cells inside the battery may experience electrode dislocation, cracked solder joints, etc., resulting in sudden changes in battery voltage, power outages, performance degradation, and even safety failures.
[0003] CN202011496591.8 A lithium-ion battery with a shockproof structure, through the design of a shock-absorbing component, buffers and absorbs the vibrations of the battery body assembly in the upper, lower, left and right positions in the protective box, prevents the outer wall of the battery and the internal electronic components from being compressed and abraded, increases the service life of the battery, and ensures the working safety of the battery. This invention mainly performs shockproofing of the battery pack by designing a shock-absorbing mechanism of the battery pack protective box, but this design greatly increases the weight of the battery pack and seriously reduces its energy density.
[0004] At present, the main method to improve the mechanical reliability of batteries is to optimize and improve the structural strength and shock absorption design of battery packs. By improving the structural strength of battery packs and using high-performance shock absorbers, the mechanical magnitude can indeed be significantly reduced. However, on the other hand, high-strength alloy materials and high-performance shock absorption mechanisms cause a significant increase in the weight of battery packs, which seriously affects the energy density and performance of batteries, and cannot meet the design concept and needs of miniaturization and lightweight of modern weapons and equipment. Summary of the invention
[0005] The present invention aims to solve the problems of mechanical damage, power failure, voltage mutation, performance degradation, and even fire and explosion of lithium-ion cylindrical batteries under large-scale mechanical conditions, and provides a high-mechanical-reliability lithium-ion battery. While ensuring the basic performance of the lithium-ion battery, the high-reliability application of the battery in large-scale mechanical environments is achieved.
[0006] The present invention is implemented as follows: a high mechanical reliability lithium ion storage battery comprises a shell, a battery cover and a battery cell consisting of a positive electrode, a negative electrode and a diaphragm; a circle of swelling tape is pasted on the outside of the battery cell along the edge of the diaphragm outside the battery cell, forming an elastic buffer zone between the battery cell and the shell; the swelling tape can absorb the organic solvent of the electrolyte and expand in volume, the expansion rate is not less than 200%, and can withstand a high temperature environment above 100°C; a flexible connection row with a bent shape is laser welded between the pole ear and the battery cover, the current is conducted from the inside of the battery cell to the outside of the battery, and the battery cell is inserted into the shell for assembly through bending and compression of the flexible connection row.
[0007] The flexible connection bar is a multi-layer aluminum bar or a multi-layer copper bar. When the tab bundle is an aluminum tab bundle, the flexible connection bar is a multi-layer aluminum bar. When the tab bundle is a copper tab bundle, the flexible connection bar is a multi-layer copper bar.
[0008] The flexible connection row is bent in a "C" shape, an "S" shape or a "Z" shape.
[0009] The swelling tape is bound to the outside of the battery cell along the winding direction of the outer diaphragm of the battery cell.
[0010] The multi-layer aluminum busbar is a 1.6 mm thick multi-layer aluminum busbar formed by hot pressing a 0.2 mm thick aluminum busbar at 620° C. and a pressure of 0.5 MPa for 50 seconds; the multi-layer copper busbar is a 1.2 mm thick multi-layer copper busbar formed by hot pressing a 0.16 mm thick copper busbar at 700° C. and a pressure of 0.5 MPa for 50 seconds.
[0011] The advantages and positive effects of the present invention are:
[0012] 1. The swelling tape design improves the radial stress of the battery, effectively reduces the mechanical magnitude, and ensures the radial mechanical reliability of the battery cell under a large-scale mechanical environment.
[0013] 2. The soft connection row design improves the axial stress of the battery, effectively reduces the mechanical magnitude, and ensures the axial mechanical reliability of the battery cell under a large-scale mechanical environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is a schematic diagram of the structure of the lithium-ion storage battery with high mechanical reliability of the present invention;
[0015] Figure 2 It is a schematic structural diagram of a flexible connection row of a lithium-ion battery with high mechanical reliability according to an embodiment of the present invention.
[0016] In the figure, 1. outer shell, 2. battery cover, 3. positive electrode, 4. negative electrode, 5. separator, 6. swelling tape, 7. flexible connection row. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation methods described herein are only used to explain the present invention and are not used to limit the present invention.
[0018] In the description of the present invention, it should be noted that the orientations or positional relationships indicated by terms such as “upper”, “middle”, “lower”, “inside”, “outside”, and “both sides” are based on the orientations or positional relationships shown in the accompanying drawings, and are only simplified descriptions for the convenience of describing the present invention, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0019] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "provided with", "connected", etc. should be understood in a broad sense. For example, "connected" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0020] like Figure 1 , 2 As shown, the high mechanical reliability lithium-ion storage battery of the present invention comprises a shell 1, a battery cover 2 and a battery cell composed of a positive electrode 3, a negative electrode 4 and a diaphragm 5. A circle of swelling tape 6 is pasted on the outside of the battery cell along the edge of the diaphragm outside the battery cell, forming an elastic buffer zone between the battery cell and the shell 1. The swelling tape 5 can absorb the organic solvent of the electrolyte and expand in volume, with an expansion rate of not less than 200%, and can withstand a high temperature environment above 100°C; a flexible connection row 7 with a bent shape is laser-welded between the pole ear and the battery cover 2, so that the current is conducted from the inside of the battery cell to the outside of the battery, and the flexible connection row 7 is bent and compressed to allow the battery cell to be inserted into the shell 1 for assembly.
[0021] The flexible connection bar 7 is a multi-layer aluminum bar or a multi-layer copper bar. When the tab bundle is an aluminum tab bundle, the flexible connection bar 7 is a multi-layer aluminum bar. When the tab bundle is a copper tab bundle, the flexible connection bar 7 is a multi-layer copper bar.
[0022] The flexible connection row 7 is bent in a "C" shape, an "S" shape or a "Z" shape.
[0023] The swelling tape 6 is bound to the outside of the battery cell along the winding direction of the outer separator of the battery cell.
[0024] The multi-layer aluminum busbar is a 1.6 mm thick multi-layer aluminum busbar formed by hot pressing a 0.2 mm thick aluminum busbar at 620° C. and a pressure of 0.5 MPa for 50 seconds; the multi-layer copper busbar is a 1.2 mm thick multi-layer copper busbar formed by hot pressing a 0.16 mm thick copper busbar at 700° C. and a pressure of 0.5 MPa for 50 seconds.
[0025] Specifically, the battery cell of the present invention is formed by winding the positive electrode 3, the negative electrode 4, and the separator 5; the positive and negative electrode ears are respectively connected to the positive and negative electrode soft connecting bars 7 by laser welding; the swelling tape 6 is adhered to the outer side of the battery cell by pasting; the soft connecting bar is bent in a "C" manner and connected to the battery cover 2 by laser welding; after the battery cell is placed in the shell, the battery cover 2 is welded to the battery shell 1 by laser welding to form a lithium-ion battery with high mechanical reliability.
[0026] The present invention uses HS-220#3035Q swelling tape produced by Wuhu Huishi New Material Technology Co., Ltd., which is a special tape that absorbs organic solvents and expands in volume with an expansion rate of more than 200%; it can withstand high temperature environments above 100°C. The swelling tape is bound to the outside of the battery cell along the winding direction of the outer diaphragm of the battery cell, such as Figure 1 As shown in the figure, when it encounters electrolyte, it will absorb liquid and expand, thus forming an elastic buffer zone between the battery cell and the shell. When the battery cell expands during charging, the expansion force will be released first in the buffer zone, so as not to cause excessive force on the shell; at the same time, during the discharge and contraction process, the battery cell will be restrained by the buffer zone, so that the battery cell will not break free from the restraint and fail. When the battery is placed in a large-scale mechanical environment for charging and discharging, the role of the buffer zone is more obvious. The buffer zone can greatly alleviate the mechanical impact from the radial direction, effectively reduce the mechanical magnitude, and ensure the high reliability of the battery cell in a large-scale mechanical environment.
[0027] The flexible connecting bar of the present invention acts as a current collecting mechanism to conduct current from the inside of the battery cell to the outside of the battery. Figure 2As shown in the figure, the connecting bar is formed by hot pressing of a 0.16 mm thick copper bar or a 0.2 mm thick aluminum bar to form a 1.2 mm thick multi-layer copper bar or a 1.6 mm thick multi-layer aluminum bar, wherein the aluminum bar is hot pressed at 620°C and 0.5 MPa for 50 seconds; the copper bar is hot pressed at 700°C and 0.5 MPa for 30 seconds. This forming method achieves high yield strength and good toughness of the soft connecting bar while meeting the flow capacity of the soft connecting bar. The soft connecting bar is connected to the tab and the battery cover respectively by welding. Good toughness allows the soft connecting bar to be arranged in various forms inside the battery, and a single-layer or multi-layer stress buffer zone can be formed to cope with mechanical shocks of different magnitudes. When the battery is placed in a large-scale mechanical environment for charging and discharging, the single-layer or multi-layer buffer zone can greatly alleviate the mechanical shock from the axial direction, effectively reduce the mechanical magnitude, and ensure the high reliability of the battery cell in a large-scale mechanical environment.
[0028] In order to further understand the content, features and effects of the present invention, the following embodiments and comparative examples are given and described in detail as follows:
[0029] Example 1
[0030] An example of a 10Ah 33160 lithium-ion battery is given below:
[0031] Cut the swelling tape into a rectangular film with a length of 110mm±1mm and a width of 130mm±1mm, and stick the swelling tape to the outside of the battery cell along the edge of the outer separator of the battery cell. Make sure that the swelling tapes do not overlap with each other, and cut off the overlapping swelling tapes.
[0032] The tab bundle is pre-welded by laser welding, where the peak power of the aluminum tab bundle welding is 500W, the pulse width is 6.0ms, and the frequency is 7.0Hz; the peak power of the copper tab bundle welding is 700W, the pulse width is 6.0ms, and the frequency is 8.0Hz. It is ensured that the misalignment of the tab bundle in the width direction does not exceed 1mm.
[0033] The tab bundle and the flexible connection bar are welded by laser welding, where the welding power of the aluminum tab bundle and the aluminum bar is 1600W, the welding speed is 65mm / s, and the gas flow rate is 18L / min; the welding power of the copper tab bundle and the copper-nickel composite bar is 2200W, the welding speed is 75mm / s, and the gas flow rate is 18L / min. Ensure that the melting depth of the aluminum tab bundle and the aluminum bar is not less than 1.6mm, the tab tensile test is greater than 50N or the tab is broken; the melting depth of the copper tab bundle and the copper-nickel composite bar is not less than 1.2mm, the tab tensile test is greater than 50N or the tab is broken.
[0034] The flexible connector bar is welded to the battery cover and the guide body by laser welding. The welding power of the aluminum flexible connector bar and the battery cover is 2000W, the welding speed is 60mm / s, and the gas flow rate is 18L / min; the welding power of the copper flexible connector bar and the guide body is 2600W, the welding speed is 75mm / s, and the gas flow rate is 18L / min. Ensure that the welding depth of the flexible connector bar, the battery cover and the guide body is not less than 2mm.
[0035] The aluminum flexible connector and the copper flexible connector have different bending methods such as "C", "S", and "Z" according to the mechanical environmental conditions of the battery. This example uses the "S" bending method to bend and compress the flexible connector so that the battery cell can be assembled into the battery shell.
[0036] After the lithium ion battery prepared in the above manner is formed and aged, performance tests such as random vibration and mechanical impact are performed according to the mechanical property test method.
[0037] Example 2
[0038] An example of a 10Ah 4680 lithium-ion battery is given below:
[0039] Cut the swelling tape into a rectangular film with a length of 110mm±1mm and a width of 68mm±1mm, and stick the swelling tape to the outside of the battery cell along the edge of the outer separator of the battery cell. Make sure that the swelling tapes do not overlap each other, and cut off the overlapping swelling tapes.
[0040] The tab bundle is pre-welded by laser welding, where the peak power of the aluminum tab bundle welding is 560W, the pulse width is 6.0ms, and the frequency is 7.0Hz; the peak power of the copper tab bundle welding is 760W, the pulse width is 6.0ms, and the frequency is 8.0Hz. It is ensured that the misalignment of the tab bundle in the width direction does not exceed 1mm.
[0041] The tab bundle and the flexible connection bar are welded by laser welding, where the welding power of the aluminum tab bundle and the aluminum bar is 1650W, the welding speed is 65mm / s, and the gas flow rate is 18L / min; the welding power of the copper tab bundle and the copper-nickel composite bar is 2250W, the welding speed is 75mm / s, and the gas flow rate is 18L / min. Ensure that the melting depth of the aluminum tab bundle and the aluminum bar is not less than 2.0mm, the tab tensile test is greater than 50N or the tab is broken; the melting depth of the copper tab bundle and the copper-nickel composite bar is not less than 1.6mm, the tab tensile test is greater than 50N or the tab is broken.
[0042] The flexible connector bar is welded to the battery cover and the guide body by laser welding. The welding power of the aluminum flexible connector bar and the battery cover is 2000W, the welding speed is 60mm / s, and the gas flow rate is 18L / min; the welding power of the copper flexible connector bar and the guide body is 2600W, the welding speed is 75mm / s, and the gas flow rate is 18L / min. Ensure that the welding depth of the flexible connector bar, the battery cover and the guide body is not less than 2mm.
[0043] The aluminum flexible connector and the copper flexible connector have different bending methods such as "C", "S", and "Z" according to the mechanical environmental conditions of the battery. This example uses the "S" bending method to bend and compress the flexible connector so that the battery cell can be assembled into the battery shell.
[0044] After the lithium ion battery prepared in the above manner is formed and aged, performance tests such as random vibration and mechanical impact are performed according to the mechanical property test method.
[0045] Example 3
[0046] An example of a 20Ah 46120 lithium-ion battery is given below:
[0047] Cut the swelling tape into a rectangular film with a length of 110mm±1mm and a width of 105mm±1mm, and stick the swelling tape to the outside of the battery cell along the edge of the outer separator of the battery cell. Make sure that the swelling tapes do not overlap with each other, and cut off the overlapping swelling tapes.
[0048] The tab bundle is pre-welded by laser welding, where the peak power of the aluminum tab bundle welding is 560W, the pulse width is 6.0ms, and the frequency is 7.0Hz; the peak power of the copper tab bundle welding is 760W, the pulse width is 6.0ms, and the frequency is 8.0Hz. It is ensured that the misalignment of the tab bundle in the width direction does not exceed 1mm.
[0049] The tab bundle and the flexible connection bar are welded by laser welding, where the welding power of the aluminum tab bundle and the aluminum bar is 1650W, the welding speed is 65mm / s, and the gas flow rate is 18L / min; the welding power of the copper tab bundle and the copper-nickel composite bar is 2250W, the welding speed is 75mm / s, and the gas flow rate is 18L / min. Ensure that the melting depth of the aluminum tab bundle and the aluminum bar is not less than 2.0mm, the tab tensile test is greater than 50N or the tab is broken; the melting depth of the copper tab bundle and the copper-nickel composite bar is not less than 1.6mm, the tab tensile test is greater than 50N or the tab is broken.
[0050] The flexible connector bar is welded to the battery cover and the guide body by laser welding. The welding power of the aluminum flexible connector bar and the battery cover is 2000W, the welding speed is 60mm / s, and the gas flow rate is 18L / min; the welding power of the copper flexible connector bar and the guide body is 2600W, the welding speed is 75mm / s, and the gas flow rate is 18L / min. Ensure that the welding depth of the flexible connector bar, the battery cover and the guide body is not less than 2mm.
[0051] The aluminum flexible connector and the copper flexible connector have different bending methods such as "C", "S", and "Z" according to the mechanical environmental conditions of the battery. This example uses the "S" bending method to bend and compress the flexible connector so that the battery cell can be assembled into the battery shell.
[0052] After the lithium ion battery prepared in the above manner is formed and aged, performance tests such as random vibration and mechanical impact are performed according to the mechanical property test method.
[0053] Mechanical properties test:
[0054] Install the fully charged battery into the mechanical test fixture, which can perfectly fix the battery. Place the fixed battery test fixture on the vibration table and impact table, and fix them to them. According to the random vibration conditions in Table 1 and the mechanical impact conditions in Table 2, perform vibration and impact tests on the battery in radial direction (±X direction) and axial direction (±Z direction), respectively. The random vibration test time is 3 minutes, and the mechanical impact test is 3 impacts in each direction. During the test, the battery is discharged with a charging and discharging device at a discharge current of 1.0C, and the battery voltage is monitored.
[0055] Table 1 Random vibration test conditions
[0056]
[0057] Table 2 Mechanical impact test conditions (refer to GJB 360B-2009)
[0058] Frequency range / Hz Peak 50~1000 9dB / oct 1000~10000 10000g
[0059] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A lithium-ion storage battery with high mechanical reliability, comprising a housing (1), a battery cover (2) and a battery cell consisting of a positive electrode (3), a negative electrode (4) and a separator (5), characterized in that: A circle of swelling tape (6) is pasted on the outside of the battery cell along the edge of the outer diaphragm of the battery cell, forming an elastic buffer zone between the battery cell and the outer shell (1); the swelling tape (5) can absorb the organic solvent of the electrolyte and expand in volume, with an expansion rate of not less than 200%, and can withstand a high temperature environment above 100°C; a flexible connection row (7) with a bent shape is laser welded between the tab and the battery cover (2) to conduct current from the inside of the battery cell to the outside of the battery, and the battery cell is inserted into the outer shell (1) for assembly through bending and compression of the flexible connection row (7).
2. The high mechanical reliability lithium-ion battery according to claim 1, characterized in that: The flexible connecting bar (7) is a multi-layer aluminum bar or a multi-layer copper bar. When the tab bundle is an aluminum tab bundle, the flexible connecting bar (7) is a multi-layer aluminum bar. When the tab bundle is a copper tab bundle, the flexible connecting bar (7) is a multi-layer copper bar.
3. The high mechanical reliability lithium-ion battery according to claim 1, characterized in that: The flexible connection row (7) is bent in a "C" shape, an "S" shape or a "Z" shape.
4. The high mechanical reliability lithium-ion battery according to claim 1, characterized in that: The swelling tape (6) is bound to the outside of the battery cell along the winding direction of the outer diaphragm of the battery cell.
5. The high mechanical reliability lithium-ion battery according to claim 2, characterized in that: The multi-layer aluminum busbar is a 1.6 mm thick multi-layer aluminum busbar formed by hot pressing a 0.2 mm thick aluminum busbar at 620° C. and a pressure of 0.5 MPa for 50 seconds; the multi-layer copper busbar is a 1.2 mm thick multi-layer copper busbar formed by hot pressing a 0.16 mm thick copper busbar at 700° C. and a pressure of 0.5 MPa for 50 seconds.
Citation Information
Patent Citations
Lithium ion battery with shockproof structure
CN112670643A
Cited By
Jelly roll, cylindrical battery and battery pack
WO2026149550A1